Safety induction for agricultural workers in particular areas of Gadog Village in handling hazardous agrochemical exposures - Allodya Nadra Xaviera; Alya Hijrianisa; Astrid Blandina Cynthia Lubis; Elva Stiawan; G. Gunaryo (Journal of Community Service and Empowerment, 2024)
An integrated program of community service and chemical teaching has been conducted to deliver proper information to handle chemical agents that are commonly used in agricultural activities. This initiative addresses the limitation of chemical understanding among local farmers and livestock breeders regarding the safety aspect of common agrochemicals, leading to either health risks or environmental problems. Knowledge regarding agrochemical handling and disposal was delivered through presentations, discussions, and hands-on practices. Accordingly, through this community service, we encouraged agricultural workers with a basic understanding of the chemical properties of hazardous agrochemicals and the safety induction in handling and disposing of those compounds. Based on the activities carried out, the results of the pre-test and post-test showed an increase of 62% in farmers' understanding of hazardous chemicals and proper handling of these chemicals. In addition to providing some beneficial scientific information to enhance agricultural workers’ safety in their working area, an activity related to education and training of agrochemicals could increase peoples’ awareness toward hazardous chemicals that would be still freely commercialized, for example, in terms of mitigating risks associated with chemical threats.